A Theory of Takeovers and Disinvestment - LAMBRECHT, BART M.; MYERS, STEWART C. (Journal of Finance, 2007)
ABSTRACT We present a real‐options model of takeovers and disinvestment in declining industries. As product demand declines, a first‐best closure level is reached, where overall value is maximized by closing the firm and releasing its capital to investors. Absent takeovers, managers of underleveraged firms always close too late, although golden parachutes may accelerate closure. We analyze the effects of takeovers of under‐leveraged firms. Takeovers by raiders enforce first‐best closure. Hostile takeovers by other firms occur either at the first‐best closure point or too early . Closure in management buyouts and mergers of equals happens inefficiently late .